1993
DOI: 10.1007/bf01690550
|View full text |Cite
|
Sign up to set email alerts
|

Continuous veno-venous haemofiltration following cardio-pulmonary bypass

Abstract: Despite the theoretical advantages of haemofiltration and the effective control of uraemia the mortality associated with ARF following CPB remains high and is probably determined by the number of failed organs systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 17 publications
4
27
0
Order By: Relevance
“…Given the physiological advantages of HF, it is disappointing that several clinical studies have so far failed to demonstrate evidence of a survival advantage [32, 33]. There are, in our opinion, some potential explanations for this failure.…”
Section: The Effect Of Therapy On Outcomesmentioning
confidence: 88%
See 1 more Smart Citation
“…Given the physiological advantages of HF, it is disappointing that several clinical studies have so far failed to demonstrate evidence of a survival advantage [32, 33]. There are, in our opinion, some potential explanations for this failure.…”
Section: The Effect Of Therapy On Outcomesmentioning
confidence: 88%
“…Baudouin et al [32]reported a >80% mortality rate in their study of similar patients. In this series, however, CVVH was initiated much later (>8 days postoperatively) than in our patients, and the delay in initiating CVVH identified patients more likely to die.…”
Section: The Effect Of Therapy On Outcomesmentioning
confidence: 99%
“…To remove the excessive volume and inflammatory mediators, RRT might be necessary to improve prognosis. [28][29][30][31][32][33] It is known that RRT is beneficial to patients with sepsis-related MODS because of its capacity to remove cytokines; early use of RRT might improve prognosis in patients with SIRS and sepsis. [34][35][36][37] It was demonstrated that early initiation of CRRT could improve outcome in AKI patients who underwent cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment modalities included continuous haemofiltration, either arteriovenous [23,26,28-32,37,45,-46,50-53,59], venovenous [36,38,47,49,60,66] or both [34,35,44,55], slow continuous ultrafiltration [6], continuous haemodialysis, either arteriovenous [39,41,54,56,58,61,65,68], venovenous [25,31] or both [9,24,42,62,63], continuous haemodiafiltration [40,48,67,69] as well as both continuous arteriovenous haemofiltration and haemodialysis [43,57] respectively. In one study continuous RRT was combined with intermittent haemodialysis [29].…”
mentioning
confidence: 99%
“…The types of niters used were mostly polyacrylonitrile [9,24,25,28,31,[33][34][35][37][38][39][40][41][42]48,53,58,61,65,66,[68][69][70], but also polysulphone [6,23,26,30,31,36,43,[49][50][51]57] or polyamide [32,44,46,47,51,55,56,58,70] niters have been used. In some studies the type of filter prescribed was not indicated.…”
mentioning
confidence: 99%